5-Propyl-6-(p-tolylsulfanyl)pyrimidine-2,4(1H,3H)-dione - A. M. Al-Omary, Fatmah; A. Ghabbour, Hazem; A. El-Emam, Ali; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
In the title pymiridine-2,4-dione derivative, C14H16N2O2S, the dihedral angle between the six-membered rings is 66.69 (10)°. The molecule is twisted about the Cp—S (p = pyrimidine) bond, with a C—S—C—N torsion angle of 19.57 (16)°. In the crystal, adjacent molecules form inversion dimers through pairs of strong N—H...O hydrogen bonds, generating an R2/2(8) ring motif. The dimers are connected into chains extending along the c-axis direction through additional N—H...O hydrogen bonds.